2020
DOI: 10.1101/2020.07.02.184481
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hidden genomic diversity of SARS-CoV-2: implications for qRT-PCR diagnostics and transmission

Abstract: The COVID-19 pandemic has sparked an urgent need to uncover the underlying biology of this devastating disease. Though RNA viruses mutate more rapidly than DNA viruses, there are a relatively small number of single nucleotide polymorphisms (SNPs) that differentiate the main SARS-CoV-2 clades that have spread throughout the world. In this study, we investigated over 7,000 SARS-CoV-2 datasets to unveil both intrahost and interhost diversity. Our intrahost and interhost diversity analyses yielded three ma… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 54 publications
9
19
0
Order By: Relevance
“…Here we use a cat transmission model to show that SARS-CoV-2 genetic diversity is largely shaped by genetic drift and purifying selection. This finding is in broad agreement with recent analyses of evolutionary forces acting on SARS-CoV-2 in humans 25,[27][28][29][30][31][32] . Our results further suggest that human SARS-CoV-2 isolates are relatively well-adapted to feline hosts, and that cat models recapitulate key aspects of SARS-CoV-2 evolution in humans.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…Here we use a cat transmission model to show that SARS-CoV-2 genetic diversity is largely shaped by genetic drift and purifying selection. This finding is in broad agreement with recent analyses of evolutionary forces acting on SARS-CoV-2 in humans 25,[27][28][29][30][31][32] . Our results further suggest that human SARS-CoV-2 isolates are relatively well-adapted to feline hosts, and that cat models recapitulate key aspects of SARS-CoV-2 evolution in humans.…”
Section: Introductionsupporting
confidence: 92%
“…Our study found that overall genetic diversity in cats was low and signatures support prominent roles for genetic drift and purifying selection. The combination of low genetic diversity, genetic drift, and purifying selection are in line with recent estimates of human within-host diversity 25,[27][28][29][30][31][32] . Importantly, our study only evaluated three transmission pairs with an undefined mode of transmission in the context of a single human isolate.…”
Section: Discussionsupporting
confidence: 73%
“…Due to the recent host shift and to the fact that many mutations in SARS-CoV-2 seem to be the consequence of host immune system activity, a recent significant change in mutation rates and selective pressure in SARS-CoV-2 (associated with its introduction to humans) is likely. In fact, studies have suggested that the current G→U mutation rate of SARS-CoV-2 in humans, for example, is much higher than in its reservoir hosts [ 34 , 35 ]. Specifically, [ 34 ] estimated that the G→U mutation rate in SARS-CoV-2 increased 9-fold with its introduction in humans, possibly due to difference in ROS activity between hosts.…”
Section: Resultsmentioning
confidence: 99%
“…The resulting intra-host diversity has been shown to affect disease progression [26], tissue tropism [27], transmission risk [28], transmission heterogeneity [29], and treatment outcome [30, 31] in various RNA viruses. Recent findings indicate that the mutation rate of SARS-CoV-2 is about as high as the one observed in the SARS-CoV genome (0.80–2.38 × 10 −3 nucleotide substitutions per site per year) [32, 33]. Although coronaviruses have evolved a proofreading capability attributed to Nonstructural protein 14 resulting in lower mutation rates than other positive-sense ssRNA viruses [3436], the study of the intra-host genetic diversity of the novel SARS-CoV-2 virus remains important to gain a deeper understanding of its evolution and transmission dynamics and possible implications on its pathology.…”
Section: Introductionmentioning
confidence: 99%